2022
DOI: 10.3389/fsurg.2022.916298
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of the Fibrinogen-to-Albumin Ratio in Patients With Triple-Negative Breast Cancer: A Retrospective Study

Abstract: ObjectiveThis study aims to investigate the potential prognostic value of fibrinogen-to-albumin ratio (FAR) in patients with triple-negative breast cancer (TNBC).MethodsThis study used a retrospective design and enrolled 224 patients with TNBC treated between January 2009 and December 2014 at the Henan Provincial People’s Hospital. The receiver operating characteristic curve (ROC) was used to determine the optimal cut-off value for FAR. The associations between TNBC and clinicopathologic categorical variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“… 20 Additionally, the fibrinogen-to-albumin ratio has been identified as a potential prognostic factor for both BC 21 and triple-negative patients with BC. 22 The low fibrinogen-to-albumin ratio group demonstrated longer median disease-free survival and OS compared to the high ratio group. 22 However, another study concluded that albumin is not a reliable indicator for predicting disease aggressiveness or recurrence in BC.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“… 20 Additionally, the fibrinogen-to-albumin ratio has been identified as a potential prognostic factor for both BC 21 and triple-negative patients with BC. 22 The low fibrinogen-to-albumin ratio group demonstrated longer median disease-free survival and OS compared to the high ratio group. 22 However, another study concluded that albumin is not a reliable indicator for predicting disease aggressiveness or recurrence in BC.…”
Section: Introductionmentioning
confidence: 89%
“… 22 The low fibrinogen-to-albumin ratio group demonstrated longer median disease-free survival and OS compared to the high ratio group. 22 However, another study concluded that albumin is not a reliable indicator for predicting disease aggressiveness or recurrence in BC. 23 Prognostic and treatment-predictive factors in BC can effectively forecast clinical outcomes and aid in treatment decision-making.…”
Section: Introductionmentioning
confidence: 89%
“…8 Recently, fibrinogen-to-albumin ratio (FAR), the proportion of these two indexes, has been reported as a new inflammatory marker that is strongly associated with poor prognosis in a variety of cancers, including esophageal, hepatocellular, and breast cancers. [9][10][11] In addition, the FAR has been strongly correlated with the severity of CAD and with a poor clinical prognosis in patients with cardiovascular disease. 12,13 However, there are no data regarding the prognostic value of FAR on clinical outcomes in patients with TVD.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Initially, as a recognized marker of inflammation, FAR, which comprised fibrinogen and albumin, was a wellestablished prognostic factor in esophageal squamous cell carcinoma, breast cancer and hepatocellular carcinoma. [9][10][11] FAR was significantly associated with angiographic no-reflow, angiographic severity and adverse outcome in patients with ST-elevation myocardial infarction (STEMI) undergoing PCI. [25][26][27] Karahan et al showed that FAR was significantly related to SYNTAX score in predicting the severity of CAD in patients with STEMI.…”
mentioning
confidence: 99%